KARAKTERISTIK “AT-TAFSIR AL-HADITS” KARYA MUHAMMAD IZZAT DARWAZAH - Setyawan (STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2023)
Few of the mufassirs present their commentary products based on the order in which the surahs were descended, causing them to be less familiar and seem to have lost the historical and contextualized side when the surahs and verses were revealed to the prophet Muhammad. This is what prompted Muhammad Izzat Darwazah to come up with a product of interpretation based on the order in which the surah